2015
DOI: 10.1190/int-2014-0238.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mineralogy and organic matter on mechanical properties of shale

Abstract: We report a nanoindentation study of shales on 144 samples from Barnett, Eagle Ford, Haynesville, Kimmeridge, Ordovician, and Woodford plays. Mineralogy is found to play an important role in controlling mechanical properties of shales: An increase in carbonate and quartz content is correlated with an increase in Young’s modulus, whereas an increase in total organic content, clay content, and porosity decreases Young’s modulus. We had a close agreement between indentation moduli measured on small samples (milli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…Another is the difficulty in isolating kerogen from the shale rock because the process of extracting kerogen may damage the structure of kerogen, thereby changing its mechanical properties. To overcome this limitation, techniques such as nanoindentation are used to measure the mechanical properties of kerogen in situ. , The Young’s modulus of kerogen measured from nanoindentation measurements ranges between 6 and 15 GPa. However, the resolution of the technique is limited to the order of micrometers, and in some cases it may not be able to resolve the elastic properties of kerogen, which is often found in the submicron intergranular spaces in the shale rock.…”
Section: Introductionmentioning
confidence: 99%
“…Another is the difficulty in isolating kerogen from the shale rock because the process of extracting kerogen may damage the structure of kerogen, thereby changing its mechanical properties. To overcome this limitation, techniques such as nanoindentation are used to measure the mechanical properties of kerogen in situ. , The Young’s modulus of kerogen measured from nanoindentation measurements ranges between 6 and 15 GPa. However, the resolution of the technique is limited to the order of micrometers, and in some cases it may not be able to resolve the elastic properties of kerogen, which is often found in the submicron intergranular spaces in the shale rock.…”
Section: Introductionmentioning
confidence: 99%
“…Under normal stratigraphic conditions, the rock skeleton bore overlying formation pressure. The mechanical properties and ability to resist compaction of the shale do not strongly differ when the mineral composition and OM content are similar. ,, However, cracking and converting OM causes volume expansion and overpressure generation while increasing thermal maturity. , Thermal simulation experiments under formation conditions suggested that the highest volume of gas produced during thermal evolution was 1720 times the volume of oil . When the retention coefficient was 0.9, the maximum pressure coefficient of the Qiongzhusi Formation was 2.45 .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical properties and ability to resist compaction of the shale do not strongly differ when the mineral composition and OM content are similar. 57 , 58 , 63 However, cracking and converting OM causes volume expansion and overpressure generation while increasing thermal maturity. 64 , 65 Thermal simulation experiments under formation conditions suggested that the highest volume of gas produced during thermal evolution was 1720 times the volume of oil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical behavior of organic matter is particularly difficult to constrain and is the focus of much current research. Due to its relative softness, the mechanical behavior of shale is greatly influenced by even a few percent of this constituent (Kumar et al., 2015; Sayers, 2013; Vernik & Milovac, 2011). Various methods have been used in attempts to constrain its mechanical properties, including nanoindentation (Ahmadov et al., 2009; Zargari et al., 2013; Zeszotarski et al., 2004) and ultrasonic measurements on samples of isolated kerogen (Yan & Han, 2013).…”
Section: Introductionmentioning
confidence: 99%